Long-term outcomes and predictors of a large cohort of idiopathic retroperitoneal fibrosis patients: a retrospective study. (4th May 2019) - Zhao, J; Li, J; Zhang, Z
Abstract : Objectives : Idiopathic retroperitoneal fibrosis (iRPF) is an uncommon disease with inflammatory features. Most patients have good prognosis but some may relapse or even progress to chronic renal failure. The aims of the study were to investigate the prognosis of a large cohort of iRPF patients and explore the risk factors for poor outcomes. Methods : All patients with a definite diagnosis of iRPF in Peking University First Hospital between 1 January 2003 and 31 December 2016 were enrolled. Their clinical and laboratory data at diagnosis and subsequent follow-up visits were collected. The endpoint of follow-up was defined as disease relapse or the last follow-up. Results : In total, 155 iRPF patients (45 females, 110 males) with a mean ± sd age of 55.1 ± 12 years at diagnosis were enrolled. The median duration of follow-up was 45.3 (0.1–169.2) months. During the whole follow-up, 27/153 (17.6%) patients encountered at least one relapse. Higher baseline erythrocyte sedimentation rate (ESR) was associated with a higher risk of relapse [p = 0.021, odds ratio (OR) = 1.016, 95% confidence interval (CI) 1.002–1.029]. A longer course of glucocorticoid treatment was associated with a lower risk of relapse (p = 0.030, OR = 0.948, 95% CI 0.904–0.995). Patients with a permanent presence of hydronephrosis were more likely to develop renal atrophy (33/154 vs 19/51, χ 2  = 5.069, p = 0.024). Conclusions : Higher baseline ESR and a shorter course of glucocorticoid treatment seemed to be predictors of relapse in iRPF patients. Prompt release of hydronephrosis to prevent kidney atrophy is very important for preserving renal function and improving the prognosis.